سیاسی امور سے متعلق اسلامی اخلاقیات : وائل حلاق کے افکار کا مطالعہIslamic Ethics in Political Matters: A Study of Wael Hallaq's Thoughts (Al-Qamar, 2021)
The political and administrative matters must be stable for there to be peace and order in society. A major issue in contemporary countries is the stability of political and administrative activities. Society is deteriorating due to political and legal chaos. The Muslim countries, especially those in Asia, are where it is most noticeable. The world's nations, particularly Muslim societies, are seeing an increase in moral depravity, lack of justice and fairness, oppression and coercion, poverty and bankruptcies, as well as rising unemployment, class separation among people. According to some analysts, the immoral principles of the modern state are the primary cause of this. The contradiction between the application of the modern state and Islamic theory of ethics is growing rapidly in Muslim nations since ethics and religion are intertwined. A new moral philosophy is being sought by non-Muslim countries. As a result, Western intellectuals are hard at work laying the groundwork for postmodernist moral theory.Which moral philosophy in political and administrative issues can successfully lead to the Islamization of the modern state? Is a crucial question for academics and specialists? The ideas of Wael Hallaq can sometimes be useful in this regard. This article presents the moral philosophy of the Islamization of the modern state in light of Hallaq's ideas.
Keywords: Modern State; Islamic Law; Morality; Islamization